An introduction to empire in the New Testament - Winn, Adam, 1976- (Atlanta : SBL Press, 2016)
Explore how empire is a crucial foreground for reading and interpreting the New Testament In the last three decades, significant attention has been given to the way in which New Testament texts engage and respond to the imperial world in which they were written. The purpose of the present volume is to introduce students and non-specialists to the growing subfield of New Testament studies known as empire studies. Contributors seek to make readers aware of the significant work that has already been produced, while also pointing them to new ways in which this field is moving forward.
Striking back at the empire: empire theory and responses to empire in the New Testament / Adam Winn -- Peace, security, and propaganda: advertisement and reality in the early Roman Empire / Bruce W. Longenecker -- Jesus-in-Movement and the Roman imperial (dis)order / Richard A. Horsley -- An imperial-critical reading of Matthew / Warren Carter --The Gospel of Mark: a response to imperial propaganda / Adam Winn -- Crafting colonial identities: hybridity and the Roman Empire in Luke-Acts / Eric D. Barreto -- The fourth gospel, romanization, and the role of women / Beth M. Sheppard -- Paul and Empire 1: Romans, 1 Corinthians, 2 Corinthians / Neil Elliot -- Paul and empire 2: negotiating the seduction of imperial "peace and security" in Galatians, Thessalonians, and Philippians / James R. Harrison -- Colossians, Ephesians, and empire / Harry O. Maier -- Construing and containing an imperial Paul: rhetoric and the politics of representation in the pastoral epistles / Deborah Krause -- Resisting empire in Hebrews / Jason A. Whitlark -- Empire in James: the crown of life / Matthew Ryan Hauge -- Confronting Roman imperial claims: following the footsteps (and the narrative) of 1 Peter's eschatological Davidic shepher / Kelly D. Liebengood -- Victory and visibility: revelation's imperial textures and monumental logics / Davina C. Lopez.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Print version record.
Keywords: Bible. -- Criticism, interpretation, etc; Bible; Rome -- In the Bible; Rome in the Bible; RELIGION / Biblical Studies / New Testament; Criticism, interpretation, etc; Electronic books